In Vivo Imaging of Pancreatic Islet Grafts in Diabetes Treatment - Arifin, Dian R.; Bulte, Jeff W. M. (Frontiers in Endocrinology, 2021)
Transplantation of pancreatic islets has potential to offer life-long blood glucose management in type I diabetes and severe type II diabetes without the need of exogenous insulin administration. However, islet cell therapy suffers from autoimmune and allogeneic rejection as well as non-immune related factors. Non-invasive techniques to monitor and evaluate the fate of cell implants in vivo are essential to understand the underlying causes of graft failure, and hence to improve the precision and efficacy of islet therapy. This review describes how imaging technology has been employed to interrogate the distribution, number or volume, viability and function of islet implants in vivo. To date, fluorescence imaging, PET, SPECT, BLI, MRI, MPI and ultrasonography are the many imaging modalities being developed to fulfill this endeavor. We outline here the advantages, limitations and clinical utility of each particular imaging approach.